Waves of Matter: An Ecocritical Reading of Futurist Radia - Ferrando, Serena (Quaderni d'Italianistica, 2025)
This essay examines how the interest of Italian Futurism in radio technology coincided with early twentieth-century quantum physics discoveries and a growing awareness of the vitality of matter. In Filippo Tommaso Marinetti and Pino Masnata’s “Il teatro futurista radiofonico (La Radia)” (“The Radia: Futurist Manifesto”; 1933), radio emerged not as a conduit for human communication but as a living organism with “radiophonic sensations,” channelling the vibrations of matter. The Futurists, inspired by the quantum revelation of wave–particle duality, devised a new and hybrid creature: a being-machine that would be a dynamic, vibrational body at once material and immaterial, wave and particle. Situating radia within an ecocritical and posthumanist framework, this essay argues that, by translating scientific knowledge into aesthetic process, the Futurists transformed radio into a cosmological interface where sound, energy, and bodies intersected—an avant-gardist vision of the universe as a responsive field of wave-like co-creation.